Evaluating variability of bladder volume using ultrasound-guided radiation therapy for prostate cancer - Khaothong, Passinee; Vongsaroj, Siharach; Wattakiyanon, Nattinee; Nanna , Thongtra; Stansook, Nauljun (Journal of Thai Association of Radiation Oncology, 2022)
Background: The variation of bladder volume in IMRT and VMAT techniques for prostate cancer can lead to errors in receiving dosimetry and increase toxicity in patients. Therefore, there should be an effective system to estimate the bladder volume during radiation therapy. Objective: To evaluate the variability of bladder volume using ultrasound image guidance for radiation therapy in prostate cancers. Materials and Methods: Forty patients who were treated with a VMAT and using full urinary bladder protocol were evaluated. The patients were classified into two groups according to image guidance setup protocols (without and with using ultrasound). The first group was the patients (20 patients) who were estimated the bladder volume using the timer method before doing a CBCT. The second group (20 patients) used the ultrasound to estimate the bladder volume before doing a CBCT. A total of 429 images of CBCT including 40 images of planning CT were used to analyze. Results: There was a significant difference in the bladder volume variation between the two groups. The results found that the population-average differences of bladder volumes between planning CT and CBCT images for without and with using ultrasound guidance were 46.2±30.2% and 20.9±6.4%, respectively (p<0.0001). In addition, the bladder volume of individual patients who did not use the ultrasound also showed a higher fluctuation bladder volume in daily CBCT images than in the other group. The maximum variation for the patient who did not use ultrasound was up to ±122.5 ml with 16 repeated-CBCT images while the patients who used ultrasound found only ±69.9 ml with 1 repeated-CBCT image. Conclusion: The use of ultrasound image guidance before undergoing CBCT has significantly reduced the variation of bladder volume in prostate cancers. Moreover, this image-guidance protocol can reduce the extra-radiation dose received from repeated CBCT imaging as well as reduce time-consuming and workload in the treatment room.